Total phenolic contents, antioxidant and antimicrobial activities of Bruguiera gymnorrhiza - Haq, M.; Sani, W.; Hossain, A.B.M.S.; Taha, R.M.; Monneruzzaman, K.M. (2011)
In the present work, the antioxidant and antibacterial activities of methanolic, ethanolic and chloroform crude extract of leaves and barks of Bruguiera gymnorrhiza were investigated. The antioxidant activity of the crude extracts were evaluated using the enzymatic and non enzymatic methods namely superoxide dismutase determination, reducing power assay and 2, 2-diphenyl-1-picrylhydrazil free radical scavenging assays. Folin-ciocalteu reagent method was used to estimate the amount of total phenolic compounds of the extracts. Ethanol extract of barks showed the best result in all antioxidant assays which was positively co-related with the total phenolic contents. There was no significant difference between the IC(50) value of ethanol extract of bark and the ascorbic acid. Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus and Bacillus cereus were used as the test pathogenic bacteria in this study. Both ethanol and methanol extracts could inhibit the growth of all pathogenic bacteria while chloroform extract of leaves showed no activity against any bacteria. Antimicrobial effect of ethanol extract of barks was higher than all other extracts.